Extracellular proteases are released by ciliates in defined seawater microcosms. (August 2015) - Thao, Ngo Vy; Nozawa, Akino; Obayashi, Yumiko; Kitamura, Shin-Ichi; Yokokawa, Taichi; Suzuki, Satoru
Abstract: The biodegradation of proteins in seawater requires various proteases which are commonly thought to be mainly derived from heterotrophic bacteria. We, however, found that protists showed a high protease activity and continuously produced trypsin-type enzymes. The free-living marine heterotrophic ciliate Paranophrys marina together with an associated bacterium was isolated and used for microcosm incubation with different concentrations of killed bacteria as food for 10 days. The results showed that the co-existence of the ciliate with its associated bacterium produced a significant protease activity in both cell-associated and cell-free fractions while that in the associated bacterium only microcosm was negligible. The protease profiles are different between cell-associated and cell-free fractions, and a trypsin-type enzyme hydrolyzing Boc-Val-Leu-Lys-MCA was detected throughout the period in the presence of ciliates. This suggests that ciliates release proteases into the surrounding environment which could play a role in protein digestion outside cells. It has been previously suggested that bacteria are the major transformers in seawater. We here present additional data which indicates that protists, or at least ciliates with their specific enzymes, are a potential player in organic matter degradation in water columns. Graphical abstract: Highlights: Defined microcosm was prepared with ciliate and killed bacteria as food. Co-existence of the ciliate produced a significant protease activity in both cell-associated and cell-free fractions. Ciliates with their specific enzymes, are a potential player in organic matter degradation in water columns.